Метод планування робіт по збору врожаю безпілотними комбайнами - Шворов, С. А.; Чирченко, Д. В. (Energy and Automation, 2017)
Method for planning the harvest unmanned combinesroutesS. Shvorov, D. Chyrchenko Based on the current trends in the development of "Precision farming", in this paper proposed approach and method for optimal planning of unmanned harvesting machinery for harvesting. The main difference between the existing developed method is that planning work is considered as unit of account of each individual piece of ground with the value programmed harvest, not the all field at once. The process of work tasks and time planning is divided into two main stages: clarify the volumes of forecast crops through the use of unmanned aerial vehicles and determination plan for use of unmanned harvesting machinery. Based on the collected and processed data from UAVs this information is continuously clarified for gradual adjustment plan of harvesting. The task of scheduling harvesting solved by dynamic programming criterion maximizing amounts of harvested in the time and cost constraints on harvesting process.Over recent years a lot of companies presented their concepts and solutions of these problems, but the cost of such equipment was not profitable. However, the situation changed dramatically when many of farmers in many states of the USA, began to suffer huge losses due to lack of trained and well-trained mechanics. Each year, some areas of Agriculture lose 30 percent of their crop because of inability to timely carry out its gathering that this would need a 24-hour day, which is not physically stand the driver person. But, currently not sufficiently developed technologies and methods of planning routes unmanned harvesting machinery (UHM) depending on the availability harvest and obstacles to their movement. In addition, not solved main tasks in integrated application of unmanned aerial vehicles and unmanned harvesting machinery for effective planning and harvesting that is relevant area of research.The purpose of research - to develop a method of planning routes unmanned harvesting machinery based on availability and crop fields obstacles in areas defined using UAVs.The process of planning the content and time of the field work is divided into several stages, namely the formation of electronic maps and clarify the status of the crop at each site by using drones and determine the compromise-optimal routes harvesting machinery in fields with obstacles and complex geometric forms.  Typically, the assessment of vegetation surveys by using UAVs is determined on the basis of Normalized Difference Vegetation Index (NDVI). This index is calculated as the difference of reflection in the near infrared and red spectral regions divided by their sum. It uses a special NIR-modified camera that greatly increases the cost of capture compared with conventional photo equipment.As the results of experimental studies, ordinary digital camera can be used effectively in programming yield and identified various obstacles in the path of unmanned harvesting machinery on each portion of the field. After the shooting on an electronic map of the field based on statistical processing RGB-signals is determined by a number of contrasting characteristics of optical zones (areas). For each of these areas, experimentally calculated the volume control crop used for training the neural network. Thus, based on statistical analysis of the spectral characteristics of digital images of each site location and using the apparatus of neural networks are determined by the volume of the crop in the path of unmanned harvester that provides operational decisions for distribution, route planning and traffic control harvesting machinery at minimum cost (compared to Remote Sensing) costs.To plan the movement of information is UHM known coordinates of the area in which harvesting is planned, the initial location of each UHM and end points of the route, the coordinates of obstacles and areas without harvest obtained using UAVs. Using the the proposed method are determined such compromise-optimal routes UHM, which provide: a) minimum path of UHM; b) detour of stationary obstacles; c) detour areas without biomass (crop). That task is to find compromise-optimal trajectories of moving UHM considering the minimum length of the route, a detour obstacles and areas without biomass. This problem is solved in the given conditions by dynamic programming optimality criterion for generalized nonlinear circuit compromise.In general optimality criterion comprises three criteria. The first criterion quantitatively determines the degree of danger approaching obstacles. Second - describes the transition UHM length of each section. The third criterion determines the degree of approximation to the site without UHM biomass. Calculation of the first and third criteria is using the Land damage expert.Thus, the proposed technological bases and method of planning routes unmanned harvesting machinery, depending on the availability of crop and obstacles in the path of UHM determined using UAVs, providing higher efficiency and precision control UHM and reduce fuel consumption.